2019
DOI: 10.1371/journal.pone.0218903
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of nursing interventions that improve the quality of life of people with chronic diseases. A systematic review with meta-analysis

Abstract: Purpose The objective of this systematic review was to determine the characteristics of the interventions conducted by nurses that attempt to improve the health related quality of life (HRQoL) of people over 18 years of age with chronic diseases. Methods This systematic review with meta-analysis summarizes 24 studies, conducted in 10 countries, that evaluated HRQoL through the Short-Form Health Survey (SF). Five databases were accessed to find the available studies from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…The effect of length of intervention was influenced by outcome type in LTCs. Shorter interventions led to better mental functioning scores (Amo‐Setien et al., 2019); longer interventions improved HbA1c levels but not blood pressure (Berntsen et al., 2019). Longer case management interventions in dementia were associated with reduced institutionalisation (Pimouguet et al., 2010), but not for other care models compared to usual care (Godard‐Sebillotte et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of length of intervention was influenced by outcome type in LTCs. Shorter interventions led to better mental functioning scores (Amo‐Setien et al., 2019); longer interventions improved HbA1c levels but not blood pressure (Berntsen et al., 2019). Longer case management interventions in dementia were associated with reduced institutionalisation (Pimouguet et al., 2010), but not for other care models compared to usual care (Godard‐Sebillotte et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In one review, having a theoretical basis was associated with improved mental functioning in nursing interventions for LTCs compared to controls (details not reported; effect size = 0.331, 95% CI 0.186–0.476, n = 13), although only 21% included studies reported being based on a theory (Amo‐Setien et al., 2019). A range of theories were reported in primary studies, such as self‐management models, the theory of vulnerability and Bandura's self‐efficacy theory (Chow & Wong, 2014; Markle‐Reid et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations